(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2023)
Background: Antenatal physiotherapy is very essential for maternal and fetal health. Adequate knowledge and awareness in pregnant women plays an important role to promote its practice. Objective: The aim of this study was to assess the awareness of antenatal physiotherapy among pregnant women in rural and urban population of Maharashtra. Study design: Survey or descriptive cross-sectional study Methods: A descriptive cross-sectional study was conducted using a self generated questionnaire which included questions related to awareness of antenatal physiotherapy among 500 pregnant women in any trimester attending regular antenatal checkups in primary health centers and private maternity clinic in rural and urban populations of Maharashtra. Results: The 406 women included 208 (51%) rural women and 198 (49%) urban women with a mean age of was 23.5 (±3.39) and 26 (±2.59) respectively. Educational level influenced the awareness of physiotherapy positively. Conclusion: The study concludes that the awareness of antenatal physiotherapy and rate of referral was found to be greater in urban women. Hence the study would like to highlight the need to create greater awareness of antenatal physiotherapy at all levels of health care systems.